Evaluation of Growth, Flowering and Seed Morphology of Batflower, Tacca chantrieri Andre - Ajisyahputra, Nikko Rizky; Palupi, Endah Retno; Krisantini, Krisantini; Wiendi, Ni Made Armini; Mulyono, Joko (Department of Agronomy and Horticulture, IPB University, 2017)
Tacca chantrieri is a perennial plant belongs to Taccaceae family that has the potential to be marketed as an ornamental plant due to its unique shape and dark color inflorescence. To date, very limited publication on T. chantrieri are available. The aim of this research was to examine plant growth pattern and flower phenology of T. chantrieri from West Borneo, Indonesia, and from Queensland, Australia in relation to their potential development as ornamental pot plants. The study was extended to examine T. chantrieri seed morphology with an inclusion of an accession from Thailand. The field experiment was conducted at the Leuwikopo experimental station in Darmaga, Bogor, Indonesia. Seed morphology examination was conducted at the Histology Laboratory of Department of Agronomy and Horticulture, Faculty of Agriculture, Bogor Agricultural University. T. chantrieri from West Borneo blooms six times a year whereas the Queensland accession twice a year. West Borneo accession had smaller bractea, fewer numbers of flowers per inflorescence and shorter flower stalk than Queensland accession. In addition, T. chantrieri Queensland grew faster than Borneo with the one leaf formed every two to three weeks, whereas it was at least four weeks in the Borneo accession. Both accessions were susceptible to leaf brown spot disease caused by Cercospora taccae. T. chantrieri Queensland seeds are oval dark brown, whereas West Borneo and Thailand accessions were shaped like kidneys (reniform) with a lighter brown color. This study demonstrated that there is great diversity in T. chantrieri including plant morphology, seed shape and color, which are important for species identification and for development of T. chantrieri as ornamental pot plant.